Two homochiral EuIII and SmIII enantiomeric pairs showing circularly polarized luminescence, photoluminescence and triboluminescence. Issue 3 (23rd December 2020) - Cui, Minghui; Wang, Ai-Ling; Gao, Cong-Li; Zhou, Liming; Wu, Tao; Fang, Shaoming; Xiao, Hong-Ping; Li, Feng-Cai; Li, Xi-Li
Abstract : Homochiral Eu III  and Sm III  complexes provide an extraordinary example that integrates PL, TL and CPL photofunctions in one molecule. Abstract : Two homochiral Eu III and Sm III tris(β-diketonate) enantiomeric pairs, based on fluorinated β-diketone (Hbtfa) and enantiopure asymmetric N, N ′-donor ligands (L R and L S ), Λ-Eu(btfa)3 L R ( R -1-Eu )/Δ-Eu(btfa)3 L S ( S -1-Eu ) and Λ-Sm(btfa)3 L R ( R -2-Sm )/Δ-Sm(btfa)3 L S ( S -2-Sm ) (btfa − = 4, 4, 4-trifluoro-1-phenyl-1, 3-butanedionate and L R /L S = (–)/(+)-4, 5-pineno-2, 2′-bipyridine) were synthesized. The electronic circular dichroism (ECD) spectra confirmed their enantiomeric nature. R -1-Eu / S -1-Eu and R -2-Sm / S -2-Sm exhibit intense characteristic emissions of Eu III (red) and Sm III (orange-red) ions both in the solid state and in DCM with long lifetimes and high luminescence quantum yields. For example, the overall quantum yields reach up to 61% and 53% along with very high sensitization efficiency values of 82 and 79 for R -1-Eu in the solid state and in DCM, respectively. Notably, the corresponding values are determined to be 6.5% (solid state) and 3.1% (DCM) for R -2-Sm, which are among the highest quantum yields for rare Sm III tris(β-diketonate) luminescent complexes reported to date. Furthermore, R -1-Eu and R -2-Sm show a strong triboluminescence (TL) phenomenon visible with the naked eye in daylight. Moreover, R -1-Eu / S -1-Eu and R -2-Sm / S -2-Sm show circularly polarized luminescence (CPL) properties. Particularly, the luminescence dissymmetry factors ( g lum ) for R -2-Sm / S -2-Sm are larger than those for R -1-Eu / S -1-Eu despite the fact that Sm III complexes usually show poorer emission than Eu III homologues, which is very rare in the reported Eu III and Sm III CPL-active complexes.